Effect of biochar on seed germination and growth of Glycine max L. under induced stress of drought - Shahid, Sabrina; Asad, Fayaz; Ikram, Ikram; Zeb, Abida; Ahmad, Imtiaz; Yaseen, Tabassum (Journal of Pure and Applied Agriculture, 2024)
As a carbon-rich substance made from organic waste by pyrolysis, biochar has demonstrated encouraging promise as a soil supplement to improve soil fertility, water retention, and plant development. Therefore, this study aimed to examine the effects of biochar application on seed germination, growth parameters, moisture content, and biochemical constituents of Glycine max L. (hereafter G. max L.) under drought stress. The results show that the drought treatment (T1) had a considerably lower germination percentage. In contrast, treatments (T2 and T3) that applied 10 and 20 tons of biochar per hectare had emergence rates of 56.66% and 50.33%, respectively, without significantly changing the germination percentage. Biochar treatments (T4 and T5) exhibited a considerable improvement in germination percentage under drought stress; T4 exhibited an emergence rate of 53.33%. In T2 (17 ± 1.53), the number of roots were maximum, whereas the longest roots were found in T3 and T4, measuring 6.65 cm and 5.87 cm, respectively. Biochar considerably increased shoot length; T2 reached 17.75 ± 0.01 cm. With the use of biochar, the quantity of leaves increased; T3 had the highest count, at 13.00 ± 0.00. Biochar considerably increased the field capacity and soil moisture content, particularly in T3, where the field capacity was 16.92 ± 0.14%, demonstrating the benefit of better soil water retention. In addition, the use of biochar improved the other biochemical substances in soybeans, such as chlorophyll “a” “b”, sugar, protein, and proline contents in treatment T2 and T3, respectively. This study demonstrates that biochar treatments may be used as a viable soil amendment to enhance soybean development, growth, stress mitigation, and biochemical composition, with implications for improved agricultural yield and sustainability. Further investigation is essential to reveal the fundamental mechanisms making these benefits under different environmental conditions and to enhance biochar application procedures.